Formant frequencies of vowels produced by infants with and without early onset otitis media - Rvachew, S.; Slawinski, E.B.; Williams, M. (Canadian Acoustics, 1996)
Samples of speech/babble were recorded from 18 infants on a longitudinal basis once every 3 months between 6 and 18 months of age. Nine of the infants were treated for at least one episode of otitis media at or before 6 months of age (Early Onset group) while the remaining infants experienced no ear infections during the first 6 months of life (Late Onset group). Analysis of the F1 and F2 frequencies of vowels contained within canonical syllables revealed no age or group related differences in the mean F1 or F2 frequencies; in the standard deviation of the F1 frequencies, or in the geometric mean of the F2/F1 ratio. However, the standard deviation of the F2 frequencies increased significantly with age. At 18 months of age, the standard deviation of the F2 frequencies was significantly smaller for the Early Onset group in comparison with the Late Onset group. These findings show that recurring otitis media with early onset can result in a restricted vowel space, mirroring previously reported findings for infants with more severe, sensori-neural hearing impairment